The Role of Conceptualization in Human Cognitive Activity - Yevheniia Terniievska (Cognitive Studies | Études cognitives, 2023)
The article analyzes the cognitive process of conceptualization, which is the process and the result of the mental construction of objects and phenomena. Conceptualization consists of the structuring of knowledge the awareness of specific information. Concepts, which are the result of conceptualization, form a separate system of interrelationships and subordination and thus compose the conceptosphere of national culture. A single concept can be expressed in several ways and at the same time a single word can express different concepts. The article emphasizes that the study of conceptualization strengthens the understanding of the role of concepts in forming a picture of the world. The result of conceptualization is not just a list of formed concepts, but also a conceptosphere as a system which includes both concepts and the connections between them.